Historical stages of formation of carabid’ fauna (Coleoptera, Carabidae) of Ciscaucasia - R. S. Sigida (Юг России: экология, развитие)
Formation of carabid’ fauna Ciscaucasia has begun, possibly, in the epoch of beginning Cretaceous. There were the serious changes of landscapes during the subsequent epoch. They have led to formation of modern fauna.